INNOVATIVENESS OF QUANTITY SURVEYING FIRMS IN THE NIGERIAN CONSTRUCTION INDUSTRY - Taiwo Adegbembo; Dorcas Moyanga (Journal of Construction Project Management and Innovation)
. Quantity surveying firms (QSFs) are faced with countless challenges and fierce competitions in the construction industry that would require the continuous embrace of technological Innovations (TI) in their services and operations. Therefore, this research examines the technological innovations in QSFs with a view to establishing their innovativeness in combating the challenges and attaining competitive advantage. Census sampling was adopted to sample quantity surveying firms in Lagos and Ondo States. Questionnaires were distributed to top management of firms and the ones retrieved were adequately analyzed representing a response rate of 53%. The findings from the analysis revealed that quantity surveying firms are slightly innovative because the adoption of new software and involvement in innovative services is moderately high though the level of awareness is high. Also, the diversification of services of quantity surveying firms to other industries like mining, automobile, shipping and aeronautical is slightly low. Hence, the implication is that quantity surveying firms should adopt technological innovations in their service delivery to survive the changing demands of clients and diversify their services to other industries to be able meet the changes in the construction industry.